Effect of Defects and Solvents on Silicene Cathode of Nonaqueous Lithium–Oxygen Batteries: A Theoretical Investigation - Yu, Yang-Xin (Journal of physical chemistry. C, 2019)
Silicene has recently shown high electrochemical performance with discharging product Li2O(s) and high stability, avoiding discharging byproducts for nonaqueous lithium–oxygen batteries. At the fundamental level, little was known about the effect of defects existing in silicene surface and various solvents on the discharging and charging processes occurring in the batteries. Here, ab initio density functional theory is employed to explore the mechanisms of oxygen reduction to Li2O(s) (ORR) on discharge and the reverse reactions on pristine and defective silicenes including single vacancy (SV), double vacancies (DV), and Stone–Thrower–Wales (STW) defects. The influence of the permittivity of solvents on the adsorption energy of the ORR intermediates as well as the stability of the cathode materials in dimethyl sulfoxide (DMSO) and 1,2-dimethoxyethane (DME) is evaluated. The analysis of the calculated results suggests that the defects show higher overpotentials when compared with pristine silicene due to their stronger attraction with the ORR intermediates, especially for LiO2(s) and lithium atoms. Pristine and three defective silicenes exhibit similar electrochemical performance in different solvents and their stabilities are related to the solvents used. Our investigation identifies the role of defective structures in silicene surfaces and the stability toward DMSO and DME. High performance of silicene cathode materials for lithium–oxygen batteries can be achieved by tuning the interaction between the ORR intermediates and silicene surfaces with attached hydrophobic functional groups.